Promoting the heritage of the city of San Cristobal de La Laguna through a temporal link with a 16th century map - Fernando Pérez Nava; Isabel Sánchez Berriel; Alejandro Pérez Nava; Virginia Gutiérrez Rodríguez; Jesús Pérez Morera (Virtual Archaeology Review)
There is an increasing interest in the conservation of historical cities since they provide a link to the roots of their communities and bring cultural and economic benefits to their inhabitants. In this paper, we present an approach to promote the knowledge of the UNESCO World Heritage city of San Cristóbal de La Laguna in the Canary Islands, Spain. The city was founded in 1496 and has a unique value due to its urban design. In this work, we present a web application that allows a user to locate places and addresses of the current city in its first known map authored by Leonardo Torriani in the 16th century. To build this application we have georeferenced the ancient map in the current cartography. The georeferencing process needs the identification of homologous ground control points in the coordinate systems of both the old map and the current cartography, and the definition of a transform between them. Best results were obtained with the non-parametric natural transform interpolation leading to a global mean error of 4.9 m that reduces to 3.2 m in the historical city centre. To provide a fast response to the user of the web application, a technique to precompute offline the natural transform is presented. The web application has a simple front-end where the user fills the current city address in a form. This activates a query to obtain the geographical coordinates of the address that are transformed to map coordinates using the pre-computed transformation. These map coordinates are used by a map viewer in the front end that locates the user address in the ancient map. To test the performance of the web application, the load of the system has been analysed obtaining a latency of 1.4 s in 50 concurrent users. Results show that the web application provides accurate results in the historical centre while providing satisfactory response times. Highlights: - This study investigates the issue of georeferencing the first historic map (16th century) of San Cristóbal de La Laguna and the possibility to geolocate current city addresses. - By using the natural interpolation method, the georeferencing errors were diminished below 4 m in most of the historic city. - A user-friendly web application has been designed which precisely locates current directions in the old map providing a valuable tool for the promotion of the heritage of the city.